PENGARUH SOSIAL DAN PERSEPSI KEMUDAHAN TERHADAP MINAT MENGGUNAKAN E-COMMERCE - Yeti; Yusni; M. Yadasang, Rosfiyanti (Economics and Business Faculty UNUSIA, 2025)
This study aims to determine the influence of social influence and perceived ease of use on the interest in using e-commerce. The data collection methods used in this study were observation, documentation, and questionnaires. The data analysis methods used were validity testing, reliability testing, classical assumption testing, and multiple linear regression testing, as well as partial t-tests and simultaneous tests (F-tests). The results of the study indicate that partially, the variables of social influence and perceived ease of use have a positive and significant influence on the interest in using e-commerce. This social influence variable has a dominant influence on the interest in using e-commerce among students of the Management Study Program at Muhammadiyah University of Luwuk. This explains that students of the Management Study Program at Muhammadiyah University of Luwuk are more influenced by social influence in using e-commerce.